The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1890/es10-00148.1
|View full text |Cite
|
Sign up to set email alerts
|

Testing interactive effects of global environmental changes on soil nitrogen cycling

Abstract: Abstract. Responses of soil nitrogen (N) cycling to simultaneous and potentially interacting global environmental changes are uncertain. Here, we investigated the combined effects of elevated CO 2 , warming, increased precipitation and enhanced N supply on soil N cycling in an annual grassland ecosystem as part of the Jasper Ridge Global Change Experiment (CA, USA). This field experiment included four treatments-CO 2 , temperature, precipitation, nitrogen-with two levels per treatment (ambient and elevated), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 64 publications
(114 reference statements)
6
74
0
Order By: Relevance
“…In agreement with our results, Colman and Schimel (2013) concluded that the direct drivers of N mineralization were soil C and N as well as clay content and that precipitation drives N mineralization indirectly through its influence on soil C and N content. Regarding PDR, Niboyet et al (2011) found that experimentally increasing precipitation 50% for 8 years resulted in a 22% increase in PDR, in agreement with the positive correlation of PDR with MAP found in our study. Niboyet et al (2011) did not, however, detect sensitivity of PDR to warming of 1 ‱ C for 8 years.…”
Section: Present Climate: N Transformationssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our results, Colman and Schimel (2013) concluded that the direct drivers of N mineralization were soil C and N as well as clay content and that precipitation drives N mineralization indirectly through its influence on soil C and N content. Regarding PDR, Niboyet et al (2011) found that experimentally increasing precipitation 50% for 8 years resulted in a 22% increase in PDR, in agreement with the positive correlation of PDR with MAP found in our study. Niboyet et al (2011) did not, however, detect sensitivity of PDR to warming of 1 ‱ C for 8 years.…”
Section: Present Climate: N Transformationssupporting
confidence: 92%
“…Regarding PDR, Niboyet et al (2011) found that experimentally increasing precipitation 50% for 8 years resulted in a 22% increase in PDR, in agreement with the positive correlation of PDR with MAP found in our study. Niboyet et al (2011) did not, however, detect sensitivity of PDR to warming of 1 ‱ C for 8 years. The MAT gradient in our study spans 1.9 ‱ C (Table 1) and the negative correlation of MAT with PDR represent long-term climatic conditions rather than short-term increases that have been experimentally induced.…”
Section: Present Climate: N Transformationssupporting
confidence: 92%
“…However a fire burned two replicate blocks in July of 2003 (Henry et al 2006;Gutknecht et al 2010). The impact of the fire treatment on soil N 2 O emission rates and related processes is discussed elsewhere (Niboyet et al 2011a), and is not included in this analysis.…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…Nitrogen addition stimulates both nitrification and denitrification (Barnard et al 2005), enhancing N 2 O emissions from soils in both natural and managed ecosystems (Bouwman et al 2002;Stehfest and Bouwman 2006;van Groenigen et al 2010). Elevated CO 2 has been shown to increase and decrease nitrification and denitrification enzyme activities (Barnard et al 2005;Niboyet et al 2010Niboyet et al , 2011a, decrease and increase available N (Reich et al 2006), increase C input to soil (de Graaff et al 2006), and increase soil water content (Arnone and Bohlen 1998), all of which can affect N 2 O efflux. Although there is considerable variation, on average, elevated CO 2 increases N 2 O efflux from soils (van Groenigen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The greater availability of this ion during the wet season is influenced by precipitation and humidity (Table 2). Changes in precipitation regimes, through changes in soil moisture, significantly altered the nitrogen availability processes in the soil (Dijkstra et al, 2010 andNiboyet et al, 2011). Furthermore, this variation is also influenced by the prevailing soil in the area described by GenĂș et al (2010) as typical dystrophic Red-Yellow Argisol -PVAd (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%